TECHNOLOGY-BASED HEALTH COMMUNICATION: LEGAL REGULATION, TELEMEDICINE IMPLEMENTATION, AND PATIENT DATA PROTECTION IN THE ERA OF DIGITAL TRANSFORMATION - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (ADISAM PUBLISHER, 2025)
Technology-based health communication has experienced rapid development in the era of digital transformation, especially through the implementation of telemedicine. This development accelerates access to healthcare services, improves efficiency in diagnosis and treatment, and enables remote interaction between patients and medical personnel. However, advances in health technology also present significant regulatory challenges. Legal regulations are crucial to ensure that telemedicine services operate in accordance with professional ethics and applicable laws, and provide adequate protection for sensitive patient data. Data protection is an important aspect that must be strictly maintained to prevent the risk of leakage and misuse of health information. Effective telemedicine implementation requires close collaboration between the government, healthcare providers, and technology industry players. With strong legal regulations, safe technology implementation, and public education, an inclusive, efficient, and reliable digital healthcare ecosystem can be created